An Effectiveness Trial of PCIT for Children with and without Autism Spectrum Disorder in a Private Practice Setting. Issue 1 (2nd January 2022) - Han, Robin C.; Naguib, Suzi; Owen, Christopher K.; Druskin, Lindsay R.; Keen, Kelsey R.; Piper, Rachel; Holbert, Samantha N.; Shank, Sophia D.; Victory, Erinn J.; McNeil, Cheryl B.
ABSTRACT: Although there is a growing body of evidence that Parent–Child Interaction Therapy (PCIT) is an efficacious treatment for disruptive behaviors among children with autism spectrum disorder, further study is warranted to determine its effectiveness for this clinical population. This study examined the effectiveness of PCIT on child disruptive behavior, child compliance, and parenting behaviors among a propensity-score matched sample of 22 children with and without an autism diagnosis in a private practice behavioral health clinic. A combination of parent report and behavioral coding was used to assess changes in treatment outcomes for both groups at pre-, mid-, and post-treatment. Repeated measures analyses of variance (ANOVAs) demonstrated significant and large improvements in child disruptive behavior and parenting skills for both groups over the course of treatment. A significant and large interaction effect was found in correct parent follow-through of a discipline sequence, such that parents of children without ASD had significantly greater improvement upon completion of PCIT than did parents of children with ASD. The current study expands upon the extant literature by demonstrating the effectiveness of PCIT for children with autism spectrum disorder in a private practice setting.